Policy instruments for FDI promotion in Africa - Saskia Mösle; Frauke Steglich (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2020)
Global foreign direct investment (FDI) has increased substantially over the past decades and so has FDI in Africa. However, still only 3 percent of global FDI stocks and 1 percent of German FDI is located in Africa. There are several policy instruments that can contribute to higher investment in developing countries. The Policy Brief outlines several important investment promotion instruments of both sender and recipient countries of FDI and assesses their impact.
Keywords: 330